PENGARUH MODEL KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV PADA PEMBELAJARAN IPAS di SDN 6 SUNGAI RAYA - Ahlun Naza Ar Rasyid; Dessy Setyowati; Suriyana (STKIP Subang, 2026)
This study aims to determine the influence of the two stay two stray cooperative model on the learning outcomes of grade IV students in science learning at SDN 6 Sungai Raya. This study uses a quantitative method of the Quasi experiment design type with a Nonequivalent Control Group Design. The population in this study, namely class IVA as the experimental class consisting of 20 students and class IVB as the control class consisting of 16 students with a total of 36 students. The sample in this study were students of class IVA (experimental class) and IVB (control class) of SDN 6 Sungai Raya. In collecting samples using purposive sampling technique. The data collection technique used in this study used observation and tests. The collection technique used test questions and observation sheets. Hypothesis testing using the t-test formula (independent sample test) with the results of the Independent t Test showing that the use of the two stray two stay type cooperative learning model has a significant impact on student learning outcomes in science lessons with a significance value of 0.034, then H0 is rejected and Ha is accepted because the sig. value (2-tailed) with a significance of 0.034 is smaller than 0.05. So it can be concluded that there is an influence in the use of the two stay two stray type cooperative model on the learning outcomes of class IV science lessons at SDN 6 Sungai Raya.